The Plants Are Talking: Can We Listen? - Lupa, Minke (Auckland University of Technology, 2023)
This research explores how a sculpture practice might hold space for co-creation and collaboration with the fallen branches of native trees. How might different methods of carving and making bring me into a deeper relationship with the plant realm? Traversing concepts of syntropy, pluriversality, herbalism and indigenous cosmologies, this project considers the rhizomatic history humans share with the plant realm. Through honouring the lifeforce spirit and the ecosystems of tree branches, plants, shells, soil, and clay, I explore a ‘remembering’ of our ancestral kinship to place. Being on the autism spectrum and having heightened sensory gating channels helps me to redefine the boundaries of my being and navigate the space between beings, allowing for energetic communication. Consciousness extends bodies into a web of interrelationships, creating conscious communicative ecosystems where humans can participate. My art practice explores these microbial-like connections of entanglement and remembrance of our ancestral connections to the living world, restoring kinship to place. My intimate relationships with the plant realm sprout new mythical vegetative beings to hold me in ritual and as guides in my healing and relationship to place. These mythical beings become an invitation to listen to the plants.